Healing through Movement: Physiotherapy after Total Abdominal Hysterectomy - Chakshu Mehta; Tushara Nair (Medical Science: Recent Advances and Applications Vol. 2, 2025)
Purpose: The aim of this chapter is to highlight the role of physiotherapy in managing post-hysterectomy complications in a patient. Presentation of Case: A 40-year-old female presented with post-surgical pain and reduced functional mobility following a total abdominal hysterectomy. She reported pain around the area of incision, limiting her ability to perform daily activities such as dressing, turning in bed, rising from a seated position, using the washroom, and climbing stairs. Structured physiotherapy interventions included pain management techniques, mobility exercises, core strengthening, and functional retraining. Results: The Numerical Pain Rating Scale (NPRS) showed a decrease in pain scores over the course of physiotherapy, while the Patient Specific Functional Scale (PSFS) demonstrated an improvement in her ability to perform daily activities. Conclusion: Physiotherapy played a key role in the post-operative rehabilitation of this patient, leading to significant improvements in pain and functional abilities. The use of the Numerical Pain Rating Scale (NPRS) and Patient Specific Functional Scale (PSFS) as outcome measures effectively tracked progress, demonstrating the positive impact of physiotherapy in post-hysterectomy recovery. This case highlights the importance of early intervention and individualized rehabilitation programs in optimizing patient outcomes.